ANALISIS PROSES HARMONISASI RANCANGAN PERATURAN DAERAH PROVINSI RIAU SEBAGAI BAGIAN PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Ulhaq, Kaafin; Haryono, Dodi; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Harmonization the draf regional regulation is an attempt to harmonize,adjusting, strengthening and rounding up the conception of a draf regionalregulatios, wheter higher, equal or more low, and other matters other than lawsand regulation, so that they are arranged systematically, not conflicting oroverlappig, regional regulations in Riau Province must of course be inaccordance with the principles of forming laws and regulations and providiondthat are in accordance with the philosophy o Pancasila and local wisdom.This research is a sociological legal research, this is based on fieldresearch which refers to interviews and observations statements as wellsupporting documents that have a corelation with the background of the problemto be studied. This study uses secondary date sources consisting of primary,secondary, and tertiary legal materials. This study uses qualitative date analysisby producing a deductive method of drawing conclusions, namely drawingconclusions from that are general to things that are specific.From the results of the discussion, it can be concluded that theharmonization, rounding and strengthening of the draft Provincial RegionalRegulations was carried out by vertical agencies, in this case the Regional Officeof the Ministry of Law and Human Rights, Riau Province. Obstacles in theprocess of harmonization of Riau Province Regional Regulations are caused byseveral factors, namely: the minimum number of human resources, the difficultyof adjusting time between agencies, and the limited budget resulting in norescheduling of the process. Efforts that need to be made so that theharmonization of the Riau Province Regional Regulation Draft can beimplemented is by providing an adequate number of human resources to carry outthe harmonization, the obligation of the relevant parties to be present whendiscussing harmonization, and the existence of an adequate budget to guaranteelegal products in the form of Regional Regulations.Keyword: Harmonization, Regional Regulation, Riau province.